The problem of anemia in elderly patients - Nieciecka, Adrianna; Paszkowska, Aleksandra; Kędziora-Kornatowska, Kornelia; Lamch, Magdalena; Jabłońska, Monika; Janiszewska, Marta; Błasik, Natalia; Groszyk, Patryk (Journal of Education, Health and Sport, 2022)
Introduction and purpose: As healthcare develops, life expectancy increases. This makes anemia of the elderly an increasingly common problem. The appearance of this disease is influenced by many factors related to the aging process of the organism. The purpose of this study is to review information about the different mechanisms of anemia development in the elderly and to present the associated difficulties in medical practice. Description of the state of knowledge: Many different factors can affect the process of anemia. The causes of this disorder include chronic inflammatory diseases, cancer and nutritional deficiencies. Endocrine status is also important. The chronic inflammatory process may induce haemolysis and lead to the increased synthesis of hepcidin, which by blocking the activity of ferroportin leads to a decrease in the level of iron ions in the blood. Deficiency anemia often results from reduced appetite, inadequate quality of meals, chronic inflammation or taking medications without consulting a doctor. The consequence is a reduced level of iron and vitamin B12 and folic acid, which play a role in erythropoiesis. The hormones that play a significant role in the process of making red blood cells include erythropoietin, testosterone and thyroid hormones. Summary: Anemia is a common problem among geriatric patients and one of the factors contributing to the increase in mortality in this age group. In medical care it is difficult to distinguish which symptoms are pathological and which are related to the natural aging process, overlapping symptoms of many diseases and related diagnostic problems. Diagnostics is a particular challenge due to the multi-morbidity, which is associated with taking many drugs with different mechanisms of action and side effects. Keywords: anemia; aging; comorbidity; nutrient-deficiency anemia; inflammation